Diskriminasi Terhadap Penyandang Disabilitas Pada Novel Invalidite Karya Faradita - Aprizal Purnama Aji (PIKTORIAL : Journal of Humanities, 2021)
This writing is a proof of acts of discrimination against persons with disabilities in Faradita's third edition of Invalidite novel which was published in 2019. This writing uses Blank and Dabady's discrimination theory, social interaction, and the impact of acts of discrimination against persons with disabilities in the umbrella of literary sociology. The method used in this study is a qualitative method where this method is used in translating data relating to acts of discrimination, social interactions and impacts with the environment. At this writing, 23 data were found on acts of discrimination against persons with disabilities, social interactions and social impacts. These actions are in the form of deliberate and obvious discrimination, subtle discrimination, unconsciously and automatically, discrimination based on data and profiles, discrimination in organizational processes. In addition, there are dissociative interaction pat-terns of competition, contravention, and conflict. Keywords: literary sociology, discrimination, patterns of social interaction